PERAN PARTISIPASI MASYARAKAT DALAM PROSES PERUMUSAN KEBIJAKAN PUBLIK DI ERA DESENTRALISASI - Fanila Kasmita Kusuma (Media Bina Ilmiah, 2024)
The decentralization era in Indonesia, marked by the implementation of regional autonomy, has significantly transformed governance structures, particularly in the formulation of public policy. One of the key elements in this transformation is the growing demand for community participation as a form of participatory democracy. This study aims to analyze the role of community participation in the public policy formulation process at the local level and to identify supporting and inhibiting factors that influence the effectiveness of such participation. The research employs a qualitative approach through literature review and case studies on participatory forums such as Musrenbang (development planning forums) and public consultation forums in selected regions. The findings reveal that community participation plays a vital role in enhancing transparency, accountability, and the relevance of policies to local needs. However, its effectiveness is often constrained by limited public capacity, lack of access to information, and weak bureaucratic commitment to accommodate public aspirations. Therefore, there is a need to strengthen participatory mechanisms that are more inclusive, systematic, and sustainable, ensuring that public policies truly reflect the interests of the people. This study contributes to a deeper understanding of participation as a foundational pillar in democratic local governance